2022
DOI: 10.1039/d2ta06077a
|View full text |Cite
|
Sign up to set email alerts
|

A rhodium–cobalt alloy bimetallene towards liquid C1 molecule electrooxidation in alkaline media

Abstract: The two-dimensional metallene with ultrahigh surface area is highly active electrocatalyst in various sustainable energy devices. Meanwhile, rhodium (Rh) based nanomaterials are attracting increased attention in electrocatalysis, which show the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Two-dimensional (2D) nanostructures, with a large surface-to-volume ratio, high electron mobility, and sufficient active sites, have attracted more focus in catalytic fields. Metallene, composed of bare metal atoms with atomical thickness, possesses highly curved geometrical configurations, high density of unsaturated metal atoms, and outstanding electronic conductivity, , which has a wide range of applications in electrocatalysis. In order to decrease the adsorption energy of oxygen, the introduction of another metal into the Pd lattice is a promising strategy, which not only effectively modifies the electronic structure of Pd and thus optimizes ORR performance but also decreases the usage of noble metals. It has been reported that the PdCu alloy is considered as a more promising ORR electrocatalyst because of the suitable oxygen adsorption energy . However, the anisotropic 2D ultrathin bimetallic nanostructures possess high surface free energy, which is thermodynamically favorable to aggregation. , Therefore, developing a facile method for the construction of ultrathin 2D alloy nanomaterials for fuel cells is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) nanostructures, with a large surface-to-volume ratio, high electron mobility, and sufficient active sites, have attracted more focus in catalytic fields. Metallene, composed of bare metal atoms with atomical thickness, possesses highly curved geometrical configurations, high density of unsaturated metal atoms, and outstanding electronic conductivity, , which has a wide range of applications in electrocatalysis. In order to decrease the adsorption energy of oxygen, the introduction of another metal into the Pd lattice is a promising strategy, which not only effectively modifies the electronic structure of Pd and thus optimizes ORR performance but also decreases the usage of noble metals. It has been reported that the PdCu alloy is considered as a more promising ORR electrocatalyst because of the suitable oxygen adsorption energy . However, the anisotropic 2D ultrathin bimetallic nanostructures possess high surface free energy, which is thermodynamically favorable to aggregation. , Therefore, developing a facile method for the construction of ultrathin 2D alloy nanomaterials for fuel cells is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33] These features would not only ensure the feasible manipulation of reactant/intermediate chemisorption toward target ECH but also provide a reliable platform with well-dened atomic arrangements and electronic congurations to unravel the electrocatalytic mechanism. 30,34 However, the relevant knowledge is still absent in the ECH of nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…A carbon-neutral society depends on a sustainable energy system for high-efficiency energy conversion. 1–5 Direct methanol/ethanol fuel cells (DMFCs/DEFCs) can use the biomass-derived renewable fuels and possess high energy density, being promising candidates for such energy systems. 4,6,7 Compared with methanol, ethanol shows higher theoretical energy density (8.01 vs. 6.09 kW h kg −1 ) and lower permeability in membranes, 4 being more plausible as a fuel.…”
Section: Introductionmentioning
confidence: 99%
“…However, the powdery catalysts lm can easily peel off during long-term testing, especially at large current density and under turbulent electrolyte ow in practical applications. 19 Compared with powdery oxides, the use of bulk nickel metal can mitigate the above drawbacks and offer certain advantages: (1) the generation of a dense surface oxide layer on the bulk nickel surface is inevitable, meaning that active NiOOH on the surfaces of bulk nickel metal can be also generated for the EOR in alkaline solution; 16,20 (2) bulk nickel metal can be easily processed and manufactured into various shapes according to the practical requirements, which allows it to serve as both a substrate for conducting current and as a catalyst for enhancing EOR, promising long-term stability. 19,21 However, the surface area of bulk nickel metal is severely decreased when compared with its powdery counterparts, meaning there are much fewer active sites for the former case.…”
Section: Introductionmentioning
confidence: 99%